3(2x+7)=-48+63

Simple and best practice solution for 3(2x+7)=-48+63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+7)=-48+63 equation:


Simplifying
3(2x + 7) = -48 + 63

Reorder the terms:
3(7 + 2x) = -48 + 63
(7 * 3 + 2x * 3) = -48 + 63
(21 + 6x) = -48 + 63

Combine like terms: -48 + 63 = 15
21 + 6x = 15

Solving
21 + 6x = 15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + 6x = 15 + -21

Combine like terms: 21 + -21 = 0
0 + 6x = 15 + -21
6x = 15 + -21

Combine like terms: 15 + -21 = -6
6x = -6

Divide each side by '6'.
x = -1

Simplifying
x = -1

See similar equations:

| 2z=-4z-2 | | 3x+30=3x+30 | | (7x-3)+(12x-7)=189 | | -x+6=2x | | 3x-(x+1)=-3+4(x-5) | | -4(x+8)=18-6(x-5) | | 4.5(2r-6)-3r= | | -4+y=-3 | | 1.6x=8.32 | | -3(x+5)=7+12(x-2) | | -4(3-3x)+7x=-37-6x | | 3x-2(7-2x)=10 | | -4=v-9 | | -3(2y-5)=7(y-2) | | 7(x-7)-4=-40-6x | | -(4x-9)-(3x-7)+6=-6(x-9)-(5x+6)+5 | | Y-3=0.4(x+1) | | R+6=-14 | | 5m+0.50=11.50 | | okx^3=343 | | m+0.50=11.50 | | -8+p=6p-6-3p | | 12x+8=8x+(-20) | | 6x-36=6 | | 5(2x-3)+4=4(2x+1)-7 | | 30=7.5x^2 | | 6(6-6p)=36+5p | | x^6-5x^4+4x^2+x+8=0 | | 2z=4z-2 | | -4(3+a)-6(1-a)=-8 | | -12=4(w-5)-6w | | -4(3+a)-6(1-a)=8 |

Equations solver categories